Waiting to Inhale: Marijuana, Medicine and the Law - Riffe, Jed (Jed Riffe Films, LLC, 2005)
Verzio FF Submission Duration: 01:14:00 “Waiting to Inhale” examines the controversy over legalizing medical marijuana in the United States, creating a dynamic portrait of patients and activists on both sides of the battle. Twelve states have passed legislation to protect patients who use medical marijuana. Yet opponents claim the medical argument is just a smokescreen for a different agenda - to legalize marijuana for recreation and profit. What claims are being made, and what are the stakes? Is marijuana really a gateway drug? What evidence is there to support the claim that marijuana can alleviate some of the devastating symptoms of AIDS, cancer and multiple sclerosis? “Waiting to Inhale” takes the viewers inside the lives of patients who have been forever changed by illness—and parents who lost their children to addiction, and sheds new light on this controversy.